Determining the Effect of Aqueous Extract of Truffle on Some Antioxidants in Rats Exposed to Oxidative Stress Induced by Hydrogen Peroxide - Hani Sabbar Ayed; Abdulkhaleq Sulaimain Khalaf; Taha Mohammed Taki Mohammed (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
The present study dealt with using of hydrogen peroxide with 0.5% with drinking water to induce state of oxidative stress in male rats and estimate the ability of different concentrations of the aqueous extract of Truffle Water Extract to reduce the effects of oxidative stress during periods 0,15,30 days by measuring the following parameters in serum: Glutathione(GSH) , Malondialdehyde (MDA), the activity of super oxide dismutase enzyme (SOD) and the peroxynitrate radical (ONOO). 50 male rats, aged 3 to 4 months, weighing 300 to 400 g, were divided into 5 groups. group (1) received tap water as the control group, group (2) had H2O2 0.5% added to the water, group (3) had H2O2 and 20% truffle water extract, group (4) had H2O2 and 40% truffle water extract, and group (5) had H2O2 and 60% truffle water extract. When compared to the control group, hydrogen peroxide treatment significantly reduced (P 0.05) the GSH and SOD activities while increasing the levels of MDA and ONOO in the serum. The results of applying different concentrations of Truffle Water Extract on rats demonstrated a slight protection against oxidative stress caused by Hydrogen Peroxide, because its influence was affected on the levels of GSH, SOD, MDA, and ONOO in the blood serum at different experiment periods.